A microemulsão de galato de octila exerce ação antitrombótica em ratos - Oliveira, Júlio César Pinheiro Lúcio de (2024)
Octyl gallate is a phenolic compound derived from gallic acid which has an antiinflammatory and ATP antagonist action, as well as low toxicity. However, no studies of this molecule on the cardiovascular or hemostatic systems have been described in the literature. However, its low solubility in water has been an obstacle to its application and pharmacological research. In this sense, this study aims to develop a microemulsion of octyl gallate (MEGO) for application as a platelet antiaggregant, anticoagulant, vasorelaxant and antithrombotic. The MEGO was produced with Cremophor EL, medium-chain triglycerides and deionized water, following a BoxBehnken factorial design. The optimized microemulsion presented droplets with an average size of 40 ± 6 nm, a zeta potential of -15 ± 0,48 mV and a polydispersity index (PdI) of 0,198 ± 0,008, remaining stable for a period of 6 months when stored at 4°C. Hemolysis tests were carried out to assess the safety of MEGO for intravenous application, showing that the microemulsion did not cause erythrocyte lysis. The antiplatelet and anticoagulant action on platelets and rat plasma was also investigated. These tests demonstrated for the first time the antiplatelet action of MEGO (Emax = 37.59 ± 1.49% and EC50 = 0,68 ± 0,04 µMol.L-1) when aggregation was stimulated with ADP. However, the microemulsion had no effect on prothrombin time (PT) or activated partial thromboplastin time (aPTT) in plasma incubated with MEGO. In the evaluation of the vasorelaxant action of MEGO on rat aorta, it was observed that it caused vasorelaxation in the rings both in the absence (Emax = 98.84 ± 1.4% and CE50 = 20,99 ± 1,13 µMol.L-1) and presence (Emax = 100.1 ± 3.6% and CE50 = 0,99 ± 0,08 µMol.L-1) of the endothelium, suggesting that the endothelium-dependent action was due to the stimulation of nitric oxide production, in view of the reduction in MEGO potency in the curves constructed in the presence of L-NAME, PTIO and ODQ. In view of these activities, the antithrombotic action of MEGO was evaluated in animals that received it intravenously. Treatment with MEGO 10 mg.Kg-1 increased the time to carotid obstruction by FeCl3-stimulated thrombus (time = 1,619 ± 40 s) and, surprisingly, the combination of MEGO 5 mg.Kg-1 with enoxiparin 5 mg.Kg-1 (anticoagulant) increased the time to obstruction (time = 3,627 ± 19 s) more than the individual treatments (at doses of 5 mg.Kg-1), indicating the synergism of these effects. In addition, in animals treated with MEGO and in combination with enoxiparin, the estimated thrombus weight and the thrombus area in relation to the carotid artery were lower. It was also observed that treatment with MEGO reduced platelet aggregation and that PT and TTPa were not altered. However, the combination of MEGO 5 mg.Kg-1 with enoxiparin 5 mg.Kg-1 increased TTPa both in relation to the control and the group treated with enoxiparin 5 mg.Kg-1 alone. These results highlight the therapeutic potential of MEGO as an antithrombotic agent and its possible usefulness in combination with other anticoagulants for the treatment of thrombotic disorders.